0154 Role of Noradrenergic Projection to the Preoptic Area in Regulation of Arousal. (27th May 2020) - Antila, H; Kwak, I; Covarrubias, I; Baik, J; Hong, J; Stucynski, J; Weber, F; Chung, S
Abstract: Introduction: Locus coeruleus (LC) is a noradrenergic nucleus in the brainstem involved in the regulation of attention, arousal, mood and sensory gating. LC projects to multiple brain regions and recent development of novel systems neuroscience tools allows the dissection of projection-specific LC function in more detail. One of the regions with noradrenergic projection is the preoptic area of the hypothalamus (POA). POA has been shown to contain neurons that are important for regulating sleep, and we have examined the function of the LC projection to the POA in sleep and arousal. Methods: We used optogenetics, chemogenetics, fiber photometry and in vivo electrophysiology to study the function of LC noradrenergic projection to the POA. Results: Norepinephrine release in the POA fluctuates with brain state changes indicating that the LC to POA projection may be involved in regulating sleep and arousal. Optogenetic stimulation of LC fibers in the POA promotes wakefulness. Furthermore, optogenetic stimulation of the LC fibers in the POA modulates the activity of sleep- and wake-active neurons. Conclusion: We have identified the role of the LC noradrenergic projection to the POA in the regulation of brain states. Stimulation of the LC fibers in the POA promotes wakefulness and modulates the activity dynamics of sleep- and wake-active neurons in the POA. Our results provide more detailed information about the role of this specific projection, which has been known to exist for a long time, but with insufficient in vivo evidence of its precise function. Support: Sigrid Juselius foundation, Alfred P. Sloan Research Fellowship in Neuroscience, The Whitehall foundation grant, McCabe Fund Award, NARSAD Young Investigator Award.